Prevalence of Attention-Deficit/Hyperactivity Disorder and its Comorbidity among Korean Children in a Community Population - Kim, Moon Jung; Park, Inho; Lim, Myung Ho; Paik, Ki Chung; Cho, Sungja; Kwon, Ho-Jang; Lee, Sang Gyu; Yoo, Seung-Jin; Ha, Mina (Journal of Korean medical science, 2017)
The aim of this study was to determine the prevalence of attention deficit hyperactivity disorders (ADHD) in children according to socio-demographic factors and the distribution of ADHD subtypes in a community in Korea. A screening survey using the Korean version of ADHD Rating Scale (K-ARS) was conducted between 2007 and 2008, and clinical interviews by a pediatric psychiatrist were performed for selected children between 2009 and 2010. A total of 49,573 elementary school students, between ages of 7 and 12, constituted the target population, among which 38,365 students (77.2%) and respective parents gave consent to participate. Of the participants, 200 screened children were clinically examined to confirm the diagnosis of ADHD. We estimated the prevalence of ADHD and its comorbidity in the population, after adjusting for nonresponse and nonparticipation. The prevalence of ADHD was 11.7% in boys and 5.2% in girls, with an overall prevalence of 8.5%. The combined type of inattentive and hyperactive was the most frequent at 4.7% of the whole population. Children were more likely to have ADHD if their parents were separated and had less education. Most commonly combined comorbidity was autism spectrum disorder (ASD) (10.1%). The prevalence of ADHD in the school-aged population is an essential information for improving the quality of public health mental services for evaluation and treatment of ADHD.